Cetacean distribution in the coastal waters of the Sultanate of Oman - Minton, Gianni; Collins , Tim; Findlay, Ken; Baldwin, Robert (J. Cetacean Res. Manage., 2023)
Small boat surveys were conducted between 2000 and 2003 in three main regions of Oman’s coastal waters: Muscat, the Gulf of Masirah and Dhofar. Survey data were analysed to calculate relative abundances of the seven most frequently encountered species in these areas. These include (in order of frequency) bottlenose dolphins (Tursiops sp.), long-beaked common dolphins (Delphinus capensis), humpback whales (Megaptera novaeangliae), spinner dolphins (Stenella longirostris), Indo-Pacific humpback dolphins (Sousa chinensis), Bryde’s whales (Balaenoptera sp.) and Risso’s dolphins (Grampus griseus). Other species observed include false killer whales (Pseudorca crassidens), blue whales (Balaenoptera musculus), rough-toothed dolphins (Steno bredanensis) and unidentified beaked whales. Encounter rates per distance searched were plotted by 0.1 x 0.1 degree grid cell, giving an indication of relative abundances and key areas of habitat used by each of the seven most frequently encountered species. These plots demonstrate that the nearshore areas of the Gulf of Masirah, as well as the coastal waters of Dhofar, are areas of concentration for the Arabian Sea’s recently designated Endangered subpopulation of humpback whales, as well as Indo-Pacific humpback dolphins, which are considered Near Threatened on the IUCN Red List of Threatened Species.1 The results presented here provide valuable baseline data for future research and help to inform conservation management efforts that are required to address the highly vulnerable status of the humpback whale and Indo-Pacific humpback dolphin populations in question.